Thai Wisdom for Thong-Yip Dessert Production in Central Province - Layim, Tanavit; Suteebut, Nomjit; Soteyome, Thanapop (Journal of Cultural Approach, 2024)
This study examined the body of knowledge and patterns of knowledge inheritance in the production of traditional Thai sweets, called Thong Yip, by groups from the central region of Thailand. Qualitative research was employed, utilizing documents and in-depth interviews. The primary data sources were purposefully selected, involving 18 participants, including experts in Thong Yip and local entrepreneurs in the studied area. A content analysis was conducted with the obtained data. The study revealed that the indigenous knowledge of Thong Yip production is a rich body of knowledge that has been passed down for over 300 years, spanning from the late Ayutthaya period to the present. This knowledge is deeply ingrained in individuals and is often transmitted within families or to extended relatives. If it is not transferred, it risks being lost with those individuals. To perpetuate this knowledge, relevant organizations should manage it in a clear and accessible learning format suitable for the contemporary era. The content should cover five aspects: 1) historical background; 2) materials and ingredients; 3) recipes; 4) production process; and 5) desirable characteristics of Thong Yip. The crucial knowledge management facets for sustaining Thong Yip production knowledge include: 1) knowledge acquisition; 2) knowledge storage; 3) knowledge application; and 4) knowledge transmission.